Role of stable isotope analyses in reconstructing past life-histories and the provenancing human skeletal remains: a review - Sehrawat, Jagmahender Singh; Kaur, Jaspreet (Anthropological Review, 2017)
This article reviews the present scenario of use of stable isotopes (mainly δ13C, δ15N, δ18O, 87Sr) to trace past life behaviours like breast feeding and weaning practices, the geographic origin, migration history, paleodiet and subsistence patterns of past populations from the chemical signatures of isotopes imprinted in human skeletal remains. This approach is based on the state that food-web isotopic signatures are seen in the human bones and teeth and such signatures can change parallely with a variety of biogeochemical processes. By measuring δ13C and δ15N isotopic values of subadult tissues of different ages, the level of breast milk ingestion at particular ages and the components of the complementary foods can be assessed. Strontium and oxygen isotopic analyses have been used for determining the geographic origins and reconstructing the way of life of past populations as these isotopes can map the isotopic outline of the area from where the person acquired water and food during initial lifetime. The isotopic values of strontium and oxygen values are considered specific to geographical areas and serve as reliable chemical signatures of migration history of past human populations (local or non-local to the site). Previous isotopic studies show that the subsistence patterns of the past human populations underwent extensive changes from nomadic to complete agricultural dependence strategies. The carbon and nitrogen isotopic values of local fauna of any archaeological site can be used to elucidate the prominence of freshwater resources in the diet of the past human populations found near the site. More extensive research covering isotopic descriptions of various prehistoric, historic and modern populations is needed to explore the role of stable isotope analysis for provenancing human skeletal remains and assessing human migration patterns/routes, geographic origins, paleodiet and subsistence practices of past populations.